The Effect of Different Field of View Sizes on Contrast-to-Noise Ratio of Cone-Beam Computed Tomography Units: An In-Vitro Study - Sandra Mehralizadeh; Anoosheh Niktash; AhmadReza Talaeipour (Tehran University of Medical Sciences, 2022)
Objectives: 'Field of view (FOV) size' affects the quality of radiographic images and the radiation dose received by patients. In cone-beam computed tomography (CBCT) FOV should be selected according to therapeutic purposes. While aiming for the highest diagnostic image quality, the radiation dose should be kept to a minimum to reduce the risk for patients. The purpose of this study was to assess the effect of different sizes of FOV on contrast-to-noise ratio (CNR) in five different CBCT units. Materials and Methods: In this experimental study, CBCT scans were taken from a dried human mandible containing a resin block fixed to the lingual cortex and a resin ring was used to simulate soft tissue during scans. Five CBCT units including, NewTom VGi, NewTom GiANO, Soredex SCANORA 3D, Planmeca ProMax, and Asahi Alphard 3030 were evaluated. Each unit had 3 to 5 different FOVs. Images were obtained and analyzed with ImageJ software and CNR was calculated in each image. ANOVA and T-test were used for statistical analysis (P<0.05). Results: Comparison among different FOVs of each unit showed significant CNR reductions in small FOVs (P<0.05). Similar FOV sizes of different CBCT devices were also compared and demonstrated significant differences (P<0.05). Conclusion: A direct relationship between FOV size and CNR was observed in all five CBCT units, but differences in exposure parameters of these units led to variable CNR in FOVs with similar sizes.